The frequency of Klebsiella pneumonia encoding genes for CTX-M, TEM-1 and SHV-1 extended-spectrum beta lactamases enzymes isolated from urinary tract infection - Masomeh Dehshiri; Seyed Sajjad Khoramrooz; Mohammad Zoladl; Seyed Abdolmajid Khosravani; Najmeh Parhizgari; Mohammad Hossein Motazedian; Soheyla Jahedi; Asghar Sharifi (BMC, 2018)
Abstract Background The extended- spectrum β-lactamase producing bacteria are widely spread worldwide. The productions of these enzymes cause bacterial resistance to a wide range of antibiotics. The aim of this study was to investigated the frequency of K. pneumonia encoding genes for CTX-M, TEM-1 and SHV-1 extended-spectrum beta lactamases enzymes isolated from urinary tract infection. Methods This study is cross-sectional study. All K. pneumonia isolates from urine samples, which had grown on media culture more than 105 were delivered to the medical microbiology laboratory. K. pneumonia susceptibility of 198 samples were confirmed by disk diffusion. The gene frequency of genes was determined using PCR, and analyzed using SPSS version 21 software. Finding Most of the K. pneumonia isolated from urine producing β-lactamase were resistant to cotrimoxazole (53.2%) followed by cefotaxime (50%), ceftazidime, ceftriaxone (40.3%), nalidixic acid (17.8%), amikacin and imipenem (1.6%) and meropenem (0%) respectively. Out of the 198 confirmed isolates of K. pneumonia, 62 cases (31.3%) have the gene phenotype of broad spectrum β-lactamase enzymes and highest frequency of gene phenotype was related to the SHV-1 gene (85.5%). Then in the terms of abundance from highest to lowest CTXM-3 (56.5%), CTXM-1 (27.4%), TEM-1 (16.1%) and CTXM-2 (8.1%), were respectively. Conclusion This study showed that K. pneumonia isolated from urine producing β-lactamase were resistance to a wide range of antibiotics. Due to the increasing resistance of most antibiotics, control and supervision in the use of antibiotics and identification of broad spectrum β-lactamase enzymes by phenotypic methods appears to be essential.